A New Cardiac Autonomic Function Predictor (Heart Rate Turbulence) in Patients with Ankylosing Spondylitis - Ersel Onrat; Seçil Demirdal; Hüseyin Dursun; Tuncay Çakır; Celal Kilit; Alaettin Avşar; Vural Kavuncu (Archives of Rheumatology, 2010)
Objective: Ankylosing spondylitis (AS) is a chronic systemic disease. The risk of cardiovascular morbidity and mortality is high in patients with AS. Heart rate turbulence (HRT) expresses ventriculophasic sinus arrhythmia and has been considered to reflect cardiac autonomic activity. It has been shown that HRT is an independent and powerful predictor of mortality. The aim of this study was to determine HRT changes in patients with AS in comparison with healthy controls. Materials and Methods: Thirty-seven patients with AS (28 men, 9 women; age: 42±2 years, range: 19-69 years) according to the modified New York criteria and 37 age-and gender-matched healthy control subjects without obvious cardiovascular disease (mean age: 40±2 years, range: 23-68 years) were included in this study. Mean duration of AS was 5±3 years (range: 1-20 years). All participants underwent 24-hour Holter ECG. HRT measurements, turbulence onset (TO) and turbulence slope (TS) were calculated with HRT View Version 0.60-0.1 software program. HRT was calculated in patients and healthy controls with at least one ventricular premature beat (VPB) in their Holter recordings. TO is a measure of the early sinus acceleration and TS is the measure of the rate of sinus deceleration that follows the sinus acceleration after a VPB. Results: There were no significant differences in TO and TS between AS patients and control subjects (TO-AS: -0.0004±0.008, TO-Control: -0.118±0.006; TS-AS: 12.07±1.26, TS-Control: 10.39±1.26, respectively). Conclusion: Although cardiovascular manifestation (including increased morbidity and mortality) of AS has been shown in various studies, HRT parameters, which determine the risk of sudden death, do not seem to be altered in this disease. (Turk J Rheumatol 2010; 25: 196-200)